Posterior Interosseous Nerve Palsy Caused by Parosteal Lipoma: A Case Report - Hatem Salama; Pradeep Kumar; Salah Bastawrous (Case Reports in Medicine)
An 83-year-old woman presented with weakness in her right-hand and wrist extensors and swelling in the proximal part of the right forearm. Electromyography (EMG) confirmed involvement of posterior interosseous nerve at the level of proximal forearm. MR imaging demonstrated the characteristics of lipoma which extended on the anterolateral aspect of the right forearm and at the level of the radius neck. The lesion was parosteal lipoma causing compression and paralysis of the posterior interosseous nerve without sensory deficit. In this paper, posterior interosseous nerve palsy due to compression of a parosteal lipoma recovered after excision of the lipoma followed by intensive rehabilitation for six month. Surgical excision should be performed to ensure optimal recovery from the nerve paralysis.